The Impact of the Russian-Ukrainian Conflict on the Security of the Republic of Poland - Jurek, Krzysztof (Wpływ konfliktu rosyjsko-ukraińskiego na bezpieczeństwo Rzeczypospolitej Polskiej, 2022)
This article is devoted to the presentation of the Russian-Ukrainian conflict in the context of security of the Third Republic of Poland, as well as checking and analysing the potential threats related to the warfare in the east. Potential and current threats that may affect Poland’s security were also presented. This article also measures the level of tolerance of people from Ukraine in Poland and how relations with our eastern neighbours have been developing in recent years. The most important issue is to provide the answer to the question whether the security of our country is or may be violated.
Zeszyty Naukowe Collegium Witelona, nr 45(4)/2022, s. 85-96
Keywords: war; Ukraine; Poland; conflict; wojna; Ukraina; Polska; konflikt